POSSIBLE RESERVE IN BRAZIL: LIMITS AND SUPPORTS FOR THE EFFECTIVENESS OF SOCIAL HEALTH RIGHTS (Reflection and Critique Law Magazine, 2020)
The theory of the reserve of the possible arose in Germany with the Constitutional Court's understanding that citizens can only demand from the state what can reasonably be expected. The theory has been adopted in Brazil as a reserve of the financially possible reflecting on the realization of fundamental social rights, especially health. We opted for an approach in the doctrine and analysis of judicial decisions on the subject through of judgments of the STF and Courts of second degree, identified by means of jurisprudential research, in the STF's website, using the keywords: "Right"; "Cheers"; "Existential minimum"; "budget"; And "reserve of the possible", which allowed to verify that the clause of the reservation of the possible is translated into limits and aporias for the effectiveness of the fundamental social right to health and that although the effort of the Judiciary Power, through study of the CNJ for the implementation of Parameters and guidelines for judicial decisions, there are still many discrepancies in the courts with "solitary" decisions and beyond budget issues.